Photocatalytic removal of Rhodamine B dye by SnIn4S8: Optimization of process by response surface methodology - Ali Mehrizad (آلودگی‌های محیطی و توسعه پایدار شهری)
In this study, the performance of stannum indium sulfide (SnIn4S8) was evaluated for photocatalytic degradation of Rhodamine B dye (RhB) as an environmental pollutant. Response surface methodology (RSM) was utilized to optimize the effective operating variables (initial RhB concentration, SnIn4S8 amount, solution pH, and irradiation time). Maximum removal efficiency of 81.15% was achieved under optimum conditions. This predicted result was confirmed experimentally (78.96%). The kinetics study of photocatalytic RhB removal by SnIn4S8 showed adherence to the pseudo-first-order kinetic model with a rate constant of 0.047 min-1. The outstanding performance of SnIn4S8 originated from its flowerlike hierarchical structure, which enhances light photon absorption, and increases pollutant adsorption.